2020
DOI: 10.1186/s43044-020-00070-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of a combination of sofosbuvir and daclatasvir treatment for hepatitis C virus infection on heart rate, rhythm and heart rate variability using 24-hour ECG monitoring

Abstract: Background: Direct-acting antiviral agents (DAAs) cure patients with hepatitis C virus (HCV) infection. Concerns have arisen the occurrence of significant bradyarrhythmias during treatment with DAAs. The aim of this study was to assess the impact of a DAA combination for the treatment of HCV infection on heart rate, rhythm, and heart rate variability (HRV) using 24-h ECG monitoring. Results: A prospective randomized study of 50 treatment-naïve patients with HCV infection treated with a combination of sofosbuvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…The patients who were free of ectopics at baseline did not develop any significant arrhythmia, and there was no change in mean HR and no dynamic ST-T wave change. These results match well earlier studies (20)(21)(22)(23), which concluded that different DAA protocols had no major cardiac events.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The patients who were free of ectopics at baseline did not develop any significant arrhythmia, and there was no change in mean HR and no dynamic ST-T wave change. These results match well earlier studies (20)(21)(22)(23), which concluded that different DAA protocols had no major cardiac events.…”
Section: Discussionsupporting
confidence: 92%
“…Statistical methods: Data entry and analysis was done by statistical package of social sciences "spss" version 23…”
Section: Methodsmentioning
confidence: 99%
“…We excluded the patients treated with amiodarone because DAAs may increase its concentration by inhibiting intestinal cytochrome P450 3A4 [ 20 ]. Similarly, a randomized study of 50 patients with structurally normal hearts treated with (SOF+ DCV) showed no significant effect on rhythm, heart rate, heart rate variability, or conductivity [ 21 ]. A meta-analysis including nearly 2300 HCV patients treated with SOF found that SOF was not associated with arrhythmias or significant bradycardias [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study conducted in Egypt using 24-h ECG monitoring during treatment, they reported that in non-cardiac patients receiving no cardioactive medications, the combination of sofosbuvir and daclatasvir for the treatment of HCV infection has no effect on heart rate, rhythm, conductivity, or heart rate variability. No symptomatic bradycardias, tachycardias, or syncope were reported or detected [ 18 ]. In a small sized study conducted in Italy, they concluded that in HCV patients treated with sofosbuvir and other DAAs, ECG parameter changes were mild and/or transient and did not translate into clinically significant electrophysiological effects in the absence of amiodarone coadministration [ 19 ].…”
Section: Discussionmentioning
confidence: 99%